(untitled) (Bangladesh Journal of Microbiology, 2010)
Coccidiosis is a disease of great economic importance for the emerging poultry industry of Bangladesh. Sulfonamides have been used extensively for treatment and control of chicken coccidiosis. However, there have been complaints regarding failure of Esb3 ® (sodium sulfachloropyrazine monohydrate; Ciba-Geigy) in treating clinical coccidiosis. Therefore this study was undertaken to examine the degree of sulfonamide resistance of field coccidian isolates. Four groups of 12-day-old chicks were infected with 104 sporulated oocysts of four field coccidian isolates. Each group contains four subgroups containing 8 chicks in each subgroup, among which one subgroup remained as infected untreated control and another 3 subgroups were treated with 30% Esb3 ® @ 1 , 2, or 2.5 g/l of drinking water for 3 consecutive days. The sulfonamide resistance was assessed on the basis of faecal oocyst counts and clinico-pathological findings. There was no significant difference (p >0.05) in weight gain between untreated chicks and the chicks treated @ 1 and 2 g/l. However, a significantly higher (p <0.05) weight gains were noted in subgroups treated with Esb3 ® @ 2.5 g/l. Chicks received treated with 2 g/l Esb3 ® received similar clinical coccidiosis and histopathological changes but little less oocyst counts as found in untreated infected control chicks. Chicks treated with 2 g/l Esb3 ® did not reveal clinical coccidiosis and revealed no or very minimal oocyst counts during the treatment period. But on histopathology, arrested or stunted parasitic stages were found during the treatment period whereas flourish parasitic development with subacute-chronic ulcerative caecitis was evident following withdrawal of treatment. These findings suggest that the drug only cause an arrested parasitic development rather than killing the parasite. Therefore, an alternative to the sulfonamides needs to find out for treating and controlling chicken coccidiosis. Keywords: Chicken; Coccidiosis; Sulfonamide; Resistance DOI: http://dx.doi.org/10.3329/bjm.v25i1.4860 Bangladesh J Microbiol, Volume 25, Number 1, June 2008, pp 60-64